The origins of risk sharing: An experimental approach - Steven Gazzillo; Barry Sopher; Athena Aktipis; Lee Cronk (Rutgers University, Department of Economics, 2011)
Controversy exists about the act of giving as altruistic instead of self-interested behavior. Each side of this argument interprets similar results from similar experiments in diff erent ways. One side argues the results show that the appearance of altruistic behavior can be explained by self-interested motives. The other side argues these results are evidence of group selection,where a group member takes an action that is harmful to itself but benefi cial to the group. We consider this question using a novel approach. We create a rich experimental environment in which subjects have the ability to cooperate to improve the group's outcome by sharing their wealth in non-compulsory, non-enforceable risk-sharing arrangements. We find that average subject behavior appears to be motivated by self-interest more than group survival.
Keywords: C9; D8; 330; risk sharing; experiment; resource management; risk sharing; experiment; resource management